152 Circulating non-classical monocytes are preferentially depleted from the circulation immediately after reperfusion in stemi patients and are associated with patient outcomes. (June 2018) - Marsh, Sarah; Draganova, Lilia; Boag, Stephen E; Das, Rajiv; Shmeleva, Evgeniya V; Bagnall, Alan; Egred, Mohaned; Howard, Nicholas; Bennaceur, Karim; Zaman, Azfar; Keavney, Bernard; Ali, Simi; et al.
Abstract : Background: In patients with acute myocardial infarction (MI), monocytes are rapidly recruited to the injured tissue, where they contribute to the inflammatory milieu. Different monocyte subsets exhibit distinct roles. Classical monocytes (CD16-CCR2 +CX3CR1-) migrate to sites of injury in response to CCL2 and differentiate into inflammatory macrophage, whilst non-classical monocytes (CD16 +CCR2- CX3CR1+) patrol the endothelium where they potentially interact with Fractalkine. The aim of this project was to characterise these circulating monocyte subpopulations dynamics in ST elevation MI patients immediately following reperfusion, and evaluate their prognostic value. Methods: Flow Cytometry was used to quantify monocyte subpopulations in the blood of 59 STEMI patients the time of primary percutaneous coronary intervention for acute MI and at different times thereafter. Infarct size and microvascular obstruction (MVO) were assessed using cardiac MRI. Results: STEMI patients showed a significant drop in circulating CD16 ++monocyte counts at 90 min post-reperfusion, whereas the CD16- monocyte counts remained unchanged at this early stage. This rapid decrease in CD16 ++monocytes was greater in individuals with a larger infarct size and lower left ventricular ejection fraction (LVEF). Conclusion: This data suggests that CD16 ++monocytes during the acute phase post-MI may hold predictive value for myocardial injury and long-term patient outcome. Further work using a CX3CR1-GFP mouse model of ischemia-reperfusion (IR) is being used to investigate monocyte recruitment to the injured myocardium at 2 and 24 hours post IR and the role of Fractalkine signalling.